Decoding Autism through Ayurveda: A Holistic Exploration of Pathophysiology and Therapeutics - Meena, Kamlesh; Singhal, Harish Kumar; Rai, Dinesh Kumar; Yadav, Ashok Kumar (Journal of Complementary and Alternative Medical Research, 2025)
Autism Spectrum Disorder (ASD) encompasses a range of complex neurodevelopmental conditions characterised by repetitive behaviours and significant challenges in social communication and interaction. ASD is a heterogeneous group of neurodevelopmental conditions characterised by persistent deficits in social communication and interaction across multiple contexts, along with restricted, repetitive patterns of behaviour, interests, or activities.  The prevalence of ASD has been steadily rising worldwide, posing a significant burden on individuals, families, and healthcare systems. While notable advancements have been made in conventional therapies, there remains a critical need for comprehensive, individualised treatment approaches. This review explores the potential role of Ayurveda as a complementary or stand-alone therapy in mild cases or adjunctively in stable conditions in managing the multifaceted manifestations of ASD.  By correlating contemporary understanding of ASD with Ayurvedic principles—particularly imbalances in the Dosha (Vata, Pitta, and Kapha), along with the concepts of Agni (digestive fire) and Ojas (vital essence)—this paper examines how traditional Ayurvedic wisdom may offer valuable insights. Key Ayurvedic interventions such as Dinacharya (daily regimen), Ritucharya (seasonal regimen), Panchakarma (five-fold detoxification therapy), Rasayana (rejuvenation therapy), Medhya Rasayana (nootropic herbs), and dietary modifications (Ahara) are discussed in the context of alleviating symptoms and improving overall quality of life in individuals with ASD. By drawing parallels between biomedical and Ayurvedic models, it aims to evaluate Ayurvedic diagnostic frameworks and therapeutic strategies that may offer complementary benefits in ASD management. The qualitative synthesis aims to provide a comprehensive overview of the Ayurvedic perspective on autism spectrum disorder and to explore its potential role as a complementary or integrative therapeutic modality in ASD management. This review emphasises the pressing need for rigorous scientific validation through well-designed clinical studies, particularly randomised controlled trials, to assess the efficacy and safety of Ayurvedic treatments for ASD. An integrative model that combines the strengths of both conventional and traditional systems of medicine may offer a more holistic and effective approach to ASD management. Ayurveda offers a holistic and individualised approach that aligns well with the complex nature of autism spectrum disorder.  Collaborative research between Ayurvedic and modern medical systems is vital to establish effective, evidence-based, and truly integrative care strategies.